Seismic hazard assessment of the central North Anatolian Fault (Turkey) from GPS-derived strain rates and b-values - Asli Dogru; Ethem Gorgun; Bahadir Aktug; Haluk Ozener (Geomatics, Natural Hazards & Risk, 2018)
The North Anatolian Fault (NAF) represents one of the most seismically active transform zones on Earth. It is characterized by high rates of crustal deformation that generate destructive earthquakes. These rates are induced by convergence of the northward-migrating Arabian and African plates with respect to the stable Eurasian plate. Therefore, the NAF represents a natural earthquake laboratory with a wide range of earthquake sizes (M ≤ 7.9) to investigate by using interdisciplinary approaches (seismological, magnetism, geological, gravitational, and geodetic studies). In this study, we compare the results of an analysis of b-values from seismicity and GPS (Global Positioning System) measurements of the strain rate to understand their coupling in terms of faulting and earthquake hazard implications. In particular, this comparison allows investigation of the spatial correlation between b-value and strain rate maps and is thus able to locate fault segments that have a high potential of generating large earthquake(s). b-Values range from 0.5 to 1.5 along the central NAF. The maximum principal strain rates are positive (tensile), and the minimum principal strain rates are negative (compressive). The surface strain is positive, showing that tensile strain is predominant in areas with high strain rates, consistent with the trend of the corresponding stresses.